FSKKP bachelor's degree project title management system - Chandrikka, Vasudavan (2014)
Final year project (FYP) or ProjekSarjanaMuda (PSM) title management process for Bachelor degree is conducted manually in the Faculty of Computer Science. This project intends to overcome the problems of PSM title management process faced by the students and lecturers. PSM title management system is a web based system that is designed to manage, organize and facilitate the process. This system comprises three modules namely students, lecturers and coordinators. Rapid application development methodology is used throughout the development of this project. The programming language toolemployed for the development of this project is PHP and MySQL for the database. The main objective of this project is to computerized the existing manual system that can help to reduce the paper work. Functionality test and user acceptance test have been conducted for this system in regards to obtain the user satisfaction feedback. In future, there should be more research on this system and new functionalities should be implemented in this system.